HDAC3 regulates the diurnal rhythms of claudin expression and intestinal permeability - Christopher, Hunter; Zhang, Jianglin; Oladejo, Sarah Olanrewaju; Sharma, Samskrathi Aravinda; Kuang, Zheng (Frontiers in Epigenetics and Epigenomics, 2024)
Circadian rhythms play an essential role in the regulation of intestinal absorption and barrier function.Tight junctions, including claudins, are fundamental components of the intestinal epithelial barrier.However, the regulatory mechanisms governing their diurnal expression remain poorly understood.Furthermore, the impact of circadian rhythms on intestinal permeability through claudin modulation has yet to be fully explored. Here we investigated the expression and the diurnal rhythms of claudin transcripts in the intestinal epithelium. We identified histone deacetylase 3 (HDAC3) as an epigenetic regulator that represses claudin expression and drives the diurnal rhythms via histone deacetylation.Loss of HDAC3 leads to increased intestinal permeability and dampened its diurnal rhythm. We further revealed that HDAC3 affects the basolateral localization of claudin-3. Together, our findings give insights into epigenetic modification in regulating tight junction and its diurnal rhythms, providing targets for therapeutic mediations in gastrointestinal disorders.